The Little Book on External Debt 2006 - World Bank (2012)
The little book on external debt, a pocket edition of the Global Development Finance (GDF) 2006, volume two, summary and country tables, contains statistical tables on the external debt of the 135 countries that report public and publicly guaranteed debt under the debtor reporting system. It also includes tables of selected debt and resource flow statistics for individual reporting countries as well as summary tables for regional and income groups. It is the culmination of a year-long process that requires extensive cooperation from people and organizations around the globe, national central banks, ministries of finance, major multilateral organizations, and many departments of the World Bank. The little book on external debt, appearing for the first time this year, provides a quick reference for users of the GDF 2006 book, CD-ROM, GDF online, and electronic subscription database. The general cutoff date for data is December 2005. The economic aggregates presented in the tables are prepared for the convenience of users. Although debt ratios can provide useful information about developments in debt-servicing capacity, conclusions drawn from them will not be valid unless accompanied by careful economic evaluation.